Association of a Chromosomal Rearrangement Event with Mouse Posterior Polymorphous Corneal Dystrophy and Alterations in Csrp2bp, Dzank1, and Ovol2 Gene Expression. - Anna L Shen; Susan A Moran; Edward A Glover; Norman R Drinkwater; Rebecca E Swearingen; Leandro B Teixeira; Christopher A Bradfield (PLoS ONE, 2016)
We have previously described a mouse model of human posterior polymorphous corneal dystrophy (PPCD) and localized the causative mutation to a 6.2 Mbp region of chromosome 2, termed Ppcd1. We now show that the gene rearrangement linked to mouse Ppcd1 is a 3.9 Mbp chromosomal inversion flanked by 81 Kbp and 542 bp deletions. This recombination event leads to deletion of Csrp2bp Exons 8 through 11, Dzank1 Exons 20 and 21, and the pseudogene Znf133. In addition, we identified translocation of novel downstream sequences to positions adjacent to Csrp2bp Exon 7 and Dzank1 Exon 20. Twelve novel fusion transcripts involving Csrp2bp or Dzank1 linked to downstream sequences have been identified. Eight are expressed at detectable levels in PPCD1 but not wildtype eyes. Upregulation of two Csrp2bp fusion transcripts, as well as upregulation of the adjacent gene, Ovol2, was observed. Absence of the PPCD1 phenotype in animals haploinsufficient for Csrp2bp or both Csrp2bp and Dzank1 rules out haploinsufficiency of these genes as a cause of mouse PPCD1. Complementation experiments confirm that PPCD1 embryonic lethality is due to disruption of Csrp2bp expression. The ocular expression pattern of Csrp2bp is consistent with a role for this protein in corneal development and pathogenesis of PPCD1.